2021
DOI: 10.3390/cancers13112742
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing of Biliary Tubulopapillary Neoplasms Reveals Common Mutations in Chromatin Remodeling Genes

Abstract: The molecular carcinogenesis of intraductal tubulopapillary neoplasms (ITPN), recently described as rare neoplasms in the pancreato-biliary tract with a favorable prognosis despite a high incidence of associated pancreato-biliary adenocarcinoma, is still poorly understood. To identify driver genes, chromosomal gains and losses, mutational signatures, key signaling pathways, and potential therapeutic targets, the molecular profile of 11 biliary and 6 pancreatic ITPNs, associated with invasive adenocarcinoma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…A final consideration of the genetic landscape of pancreatic ITPN should be reserved for chromatin remodelers, such as MLL genes and BAP1 , which seemed to be more altered in this type of lesion compared with that in conventional PDAC (although the comparison with existing datasets did not show statistical significance). Notably, a recent study on the biliary counterpart of ITPN, based on whole‐exome sequencing, confirmed the important role played by this class of genes in the whole ITPN spectrum 93 . In addition to mutations in chromatin remodelers, other correspondences of pancreatic ITPN with the biliary counterparts, further highlighting their similarities, included the common IHC profile and frequent chromosome 1q gains 93 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A final consideration of the genetic landscape of pancreatic ITPN should be reserved for chromatin remodelers, such as MLL genes and BAP1 , which seemed to be more altered in this type of lesion compared with that in conventional PDAC (although the comparison with existing datasets did not show statistical significance). Notably, a recent study on the biliary counterpart of ITPN, based on whole‐exome sequencing, confirmed the important role played by this class of genes in the whole ITPN spectrum 93 . In addition to mutations in chromatin remodelers, other correspondences of pancreatic ITPN with the biliary counterparts, further highlighting their similarities, included the common IHC profile and frequent chromosome 1q gains 93 …”
Section: Discussionmentioning
confidence: 92%
“…93 In addition to mutations in chromatin remodelers, other correspondences of pancreatic ITPN with the biliary counterparts, further highlighting their similarities, included the common IHC profile and frequent chromosome 1q gains. 93…”
Section: O L E C U L a R L A N D S C A P Ementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic alterations reported in ITPN are CDKN2A/p16 and TP53[ 108 ]. Very recently, Gross et al [ 109 ] performed whole exome sequencing of ITPN and demonstrated a high genetic diversity with recurrent copy number variants (CNVs) (loss of chromosome 1p36 and others), and only a few recurrent somatic mutations in TG, SLIT2, FGFR2, and HMCN1. They also identified cell cycle, chromatin remodelling, and DNA damage/repair as key signalling pathways in these neoplasms.…”
Section: Molecular Pathomechanismsmentioning
confidence: 99%
“…ITPN has unique genetic characteristics, including chromatin remodeling and phosphoinositide 3-kinase pathway mutations. 10,11 Owing to the rarity of this precursor lesion, the molecular mechanism and gene profiles are still unclear. In this issue of Gastroenterology, Fukunaga et al 12 identified a novel function of Arid1a in ITPN that has not been investigated in this disease before.…”
mentioning
confidence: 99%